Sex differences in functional outcomes of intravenous thrombolysis among patients with lacunar stroke - Wueger, Patrizia; Noseda, Roberta; Pagnamenta, Alberto; Bianco, Giovanni; Seiffge, David; Michel, Patrik; Nedeltchev, Krassen; Bonati, Leo; Kägi, Georg; Niederhauser, Julien; Nyffeler, Thomas; Luft, Andreas; et al. (Frontiers in Neurology, 2024)
Background This study aimed to assess if there are sex differences in the functional outcome of intravenous thrombolysis (IVT) among patients with lacunar stroke (LS). Methods Consecutive patients admitted from 1 January 2014 to 31 January 2020 to hospitals participating in the Swiss Stroke Registry presenting with LS and treated with IVT were included. The study population was then divided into two groups based on patient sex, and a multivariable ordinal logistic regression analysis was performed to uncover sex differences in the modified Rankin Scale (mRS) score at 90 days after stroke. Results A total of 413 patients with LS were treated with IVT: 177 (42.9%) women and 236 (57.1%) men. Women were older than men (median age 74 years, 25th–75th percentiles 67–84 years versus 70 years, 25th–75th percentiles 60–80 years, value of p 0.001) and, after adjustment for meaningful variables, showed more frequently increased odds of a higher mRS score at 90 days after stroke (adjusted odds ratio 1.49, 95% confidence interval 1.01–2.19, value of p 0.044). Conclusion This study showed that female sex increased the odds of a worse functional response to IVT in patients with LS. Future studies should further elucidate the mechanisms underlying such sex differences.